Development of Reading Materials for Teaching Arabic Through Android for Students In Wahid Hashim Islamic Junior High School Balung Jember - Iftitahatus Saadah; Maskud Maskud (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2022)
In the globalization era, in the 20th century, the development of Information and Communication Technology is very rapid. Even in the educational process, the teacher must be intelligent and able to choose the type of educational material he uses in the teaching and learning process. Educational materials play an essential role in the educational process and have an individual contribution to education, which impacts students. The problem in Wahid Hashim Balung Jember Islamic high school was the lack of unique education materials for reading skills. This study aims: 1) to determine the steps of developing reading materials for teaching Arabic through Android and 2) to determine the effectiveness of teaching reading materials for teaching Arabic through Android. This study uses the model approach proposed by Borg and Gall, and researchers use pre-test and post-test to develop reading materials. The results of this study showed that reading materials using Android developed by researchers effectively improve students ' reading skills. في عصر العولمة، قرن 20 أن التطورات في مجال تكنولوجيا المعلومات والإتصالات هي سريعة جدا. حتي في عملية التعليم، ينبغي للمعلم أن يكون ذاكيا وقادرا على اختيار نوع المادة التعليمية التي يستخدمها في عملية التعليم والتعلم. إن المادة التعليمية تؤدي دورا هاما في عملية التعليم ولها إسهامات الفردية في التعليم، وهذا له تأثير على التلاميذ. ومشكلات ما وقعت في المدرسة الثانوية الإسلامية واحد هاشم بالونج جمبر عدم وجود مواد التعليمية خاصة في مهارة القراءة. إن الأهداف من هذا البحث هي: 1) ولمعرفة الخطوات تطوير مادة القراءة لتعليم اللغة العربية عبر أندرويد 2) لمعرفة فعالية تعليم مادة القراءة لتعليم اللغة العربية عبر أندرويد. استخدمت الباحثة منهج البحث والتطوير بالنموذج الذي اقترحه برج وغال، واستخدمت الباحثة الإختبار القبلي والإختبار بعدي في تطوير المادة القراءة. ونتيجة هذه الرسالة هي أن المادة القراءة عبر أندرويد المطورة من الباحثة لها فعالة لترقية مهارة القراءة التلاميذ.